Population fluctuation and behavior of Paraedessa heymonsi (Breddin) and its predator Argiope sp. in Opuntia ficus-indica (l.) Mill. (Bioagro, 2022)
In the semi-arid forest of Wari (Ayacucho-Peru), the prickly pear (Opuntia ficus-indica) predominates among the plant species, and in this environment, the bedbud Paraedessa heymonsi and the spider Argiope sp. share the ecosystem. P. heymonsi infests prickly pear and Argiope sp. participates as a predator of the bedbug. The objective of the study was to determine the fluctuation and population behavior of the insect and its predator in the plant. The population of the phytophagous and its predator were evaluated fortnightly in 100 plants for a year, and the Spearman correlation was used to relate temperature, precipitation and population of Argiope sp. with the population of P. heymonsi. It was found that the population of the insect in the plant depended on the higher rainfall and temperature, and the arachnid acted as a control factor. The rainy period from January to April and from October to December favored bedbug infestation. On the contrary, the dry and cold season from April to September motivated the bug to take refuge in the tree Schinus molle L. It was concluded that the population and behavior of P. heymonsi in prickly pear is determined by the periods of highest temperature and precipitation, and by the predatory action of Argiope sp.
Keywords: Host plant; phytophagus insect; predatory spider; prickly pear